Resistências à biopolítica na educação: arte ativista na exceção brasileira - Mourão, Alexandre de Albuquerque (2013)
At first, from the perpective of a biopolitic reality and neoliberal doctrine pointed by Michel Focault, this writting will describe the interectation between the power over species and population with the concepts of "Exception State" and "Homo Sacer", which was developed by Giorgio Agamben. In addition, it will be made referance of how, themes such as the brazilian exception - the influence of military dictactorship in democracy- and education can be articulated. The aim of this dissertation is to research how the artistic intervention on urban areas about the military dictatorship, named as "education urban intervention" can be used as educational strategy in the biopolitc field. The methodology we choose was the bibliographic and documental research, books, photography, videos and images refering to the topic were used. Whatsmore, there will be presented the work of three groups, called "coletivos" which have been using those urban interventions and its strategies. The name of those are : "Aparecidos Polítcos" from Fortaleza , "Coletivo Político QUEM" from São Paulo and the national wide "Levante Popular da Juventude", This intervention are between the years 2010 and 2012 and are linked with the brazilian exception. The dissertation ends with the relationship of the studieded theories, the work of theses colectives and a demonstration at the way this educational urban interventions changes the way people see the education and the reallity.